Editorial introduction - Jermaine S. McDougald (Universidad de La Sabana, 2013)
Welcome to Volume 6, Issue 2 of the Latin American Journal of Content and Language Integrated Learning (LACLIL). This issue offers reflections on areasrelated to the integration of content and language in a variety of contexts-including Colombia, Spain, the United Kingdom, Taiwan, and Iran-in whichresearchers provide us with opportunities to reflect on current teaching practices.Globalization is making the world interconnected in ways previously un seen (Mehisto, Marsh, & Frigols, 2008, p. 10); with this in mind, the current issueof LACLIL also shows how CLIL is becoming more globalized as well, rapidly becom ing an "innovative methodology" that caters to the needs of the newgeneration at hand (Graddol, 2005 , p. 2). Nowadays, language-learning andcontent-learning are increasingly driven by learners' desires to be connected tothis globalized world, in which boundaries cease to exist, to access opportunitiesthat may not have been available beforehand.